The Effect of Job Fit And Psychological Well-Being on The Quality of Financing Decisions, With Analytical Accuracy as a Mediator Among Credit Risk Analysts (CRA) at Pnm - Siti Safaria; Elizabeth Yuli Parlina (Winter Journal: IMWI Student Research Journal, 2026)
This research aims to analyze the influence of human resource factors (HR) on the quality of financing decisions on Credit Risk Analyst (CRA) at PT Permodalan Nasional Madani (PNM). The research object includes 106 CRAs spread across 58 ULaMM branch offices throughout Indonesia, with variations in the number of CRAs per branch ranging from 1 to 3 people according to the workload and volume of financing proposals. The research used a quantitative approach with path analysis to test seven hypotheses that included direct and indirect influences between variables. The results of the study show that the suitability of CRA human resource placement has a positive and significant effect on the accuracy of financing analysis. Similarly, the psychological health of CRA has a positive and significant effect on the accuracy of financing analysis. The accuracy of financing analysis has subsequently been proven to have a positive and significant effect on the quality of financing decisions. However, the suitability of CRA's human resource placement and CRA's psychological health do not directly affect quality financing decisions. This study finds that the accuracy of financing analysis fully mediates the relationship between the suitability of CRA human resource placement and financing decision quality, as well as between CRA psychological health and financing decision quality. This implies that improving financing decisions requires strengthening financing analysis competence, rather than relying solely on placement or psychological factors.